Quantitative analysis of the physiological contributions of glucose to the TCA cycle - Liu, Shiyu (Cell Metab, 2020)
The nutritional source for catabolism in the tricarboxylic acid (TCA) cycle is a fundamental question in metabolic physiology. Limited by data and mathematical analysis, controversy exists. Using isotope-labeling data in vivo across several experimental conditions, we construct multiple models of central carbon metabolism and develop methods based on metabolic flux analysis (MFA) to solve for the preferences of glucose, lactate, and other nutrients used in the TCA cycle. We show that in nearly all circumstances, glucose contributes more than does lactate as substrate to the TCA cycle. This conclusion is verified in different animal strains from different studies, different administrations of (13)C glucose, and is extended to multiple tissue types. Thus, this quantitative analysis of organismal metabolism defines the relative contributions of nutrient fluxes in physiology, provides a resource for analysis of in vivo isotope tracing data, and concludes that glucose is the major nutrient used in mammals.